Fetal intracranial hemorrhage associated with maternal coagulopathy and vitamin K deficiency after biliary drain placement: A case report and literature review - Muhammad Abu-Rmaileh; Abigail M. Ramseyer; Lyle Burdine; Nafisa K. Dajani (Elsevier, 2021)
Introduction: Fetal intracranial hemorrhage (ICH) is a rare but serious prenatal diagnosis. Predisposing factors include maternal trauma and fetal coagulation dysfunction. Maternal vitamin K deficiency has been described as an etiology. We present a case of maternal vitamin K deficiency associated with fetal ICH after percutaneous biliary drain (PBD) placement in a complicated cholecystectomy with injury to the common bile duct. Case presentation: A 21-year-old woman, G2P1, presented at 23 weeks and 3 days of gestation with epigastric pain, nausea and vomiting. Right upper quadrant ultrasound diagnosed cholelithiasis. The patient was managed conservatively and discharged. She returned four days later, at 24 weeks of gestation, with worsening symptoms and ultrasound showing acute cholecystitis. She underwent laparoscopic cholecystectomy. Increasing bilirubin and imaging showed a transected biliary duct that required percutaneous biliary drain (PBD) placement. The patient was discharged and followed up at a high-risk obstetric clinic. Prenatal ultrasound showed bilateral ventriculomegaly with features of ICH. Maternal vitamin K deficiency was confirmed with PIVKA-II testing. The patient received vitamin K supplementation with normalization of the coagulopathy. Delivery occurred at 36 weeks of gestation via cesarean delivery after preterm premature rupture of membranes for fetal macrocrania. The neonate was discharged to a hospice. Discussion: Maternal and neonatal etiologies for ICH include malabsorption and coagulopathy. Maternal vitamin K deficiency should be considered when coagulopathy is present. This case highlights that maternal vitamin K deficiency due to biliary diversion and malabsorption increases the risk of fetal ICH, which impacts pregnancy and neonatal outcomes.